PREPARATION AND CHARACTERIZATION OF γ-AgI IN SUPERIONIC COMPOSITE GLASSES (AgI)x(AgPO3)1-x - Supandi Suminta; Evvy Kartini; T. Sakuma (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2007)
PREPARATION AND CHARACTERIZATION OF γ-AgI IN SUPERIONIC COMPOSITE GLASSES (AgI)x(AgPO3)1-x. The γ-AgI phase was stabilized at room temperature in the composites glasses (AgI)x(AgPO3)1-x with x = 0.6 and 0.7 via rapid quenching of their molten mixture. The measurement of the crystal structure has been carried out using an X-ray Difractometer at the Physics Departement of Ibaraki University, Japan. The micro strain and crystal size are derived from Hall’s equation. The X-ray diffraction pattern shows some Bragg peaks that correspond to the crystalline γ-AgI. By increasing the concentration of AgI, the peak width becomes more narrow and the position shifts to the higher angle. This indicates that the crystalline size and microstrain are increasing. The increase of micro strain (η), and particle size (D) will increase the ionic mobility, thus increasing the ionic conductivity. It is concluded that solidification process on meltAgI into glass matrix AgPO3 not only decreases the micro strain and the particle size, but it also increases the ionic conductivity.